Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1988)

QFHSA Fall Conference 1988 - Quebec Federation of Home and School Associations (QFHSA) (1988)

Submission to New Brunswick Select Committee on the 1987 Constitutional Accord Submitted by Quebec Federation of Home & School Association - Quebec Federation of Home and School Associations (QFHSA) (1988)
The Quebec Federation of Home & School Associations (QFHSA) is pleased to have the opportunity to make this submission to the Select Committee on Constitutional Reform regarding the 1987 Constitutional Accord.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1988)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1988)

1988 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1988)

QFHSA Annual General Meeting and Conference : 1988 - Quebec Federation of Home and School Associations (QFHSA) (1988)

Brief on Bill 107 "Education Act" Presented to the National Assembly Standing Committee on Education by Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1988)
The Quebec Federation of Home & School Associations (QFHSA) is pleased to have the opportunity to make this submission to Education of the National Assembly. This the Standing Committee on submission is the eighth presentation QFHSA has made to a Parliamentary Committee on school reorganization. It reflects the enduring concern of our family members that they be active and responsible participants in the setting of the framework in which their children are educated.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1988)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1988)